Ownership of Birth Certificate for Children in the Community based on Law No. 24 of 2013 concerning Population Administration (Law, Justice, and Society Perspective): Kepemilikan Akta Kelahiran Bagi Anak di Kalangan Masyarakat Berdasarkan Undang-Undang Nomor 24 Tahun 2013 Tentang Administrasi Kependudukan (Perspektif Hukum, Keadilan, dan Masyarakat) - Intani, Lutfi; Utari, Indah Sri (Annual Review of Legal Studies, 2024)
Right to a Birth Certificate guaranteed in Law No. 39 Year 1999 about Concerning Human Rights, Law No. 23 Year 2002 about Law Concerning Child Protection, Law No. 12 Year 2006 about The Indonesian Consulate General. Law No. 23 Year 2006 about Population Administration. This research aims to educate and provide rights of child that should be obtained from parents and the state. Birth Certificate is an important document that everyone should have, especially Indonesian Citizens. Birth Certificate usually registered by parents when there is a birth. Some of the benefits of a birth certificate are: confirm the lineage, obtain inheritance rights, register for education, requirements for getting a job, travelling abroad, etc. As amendment To Law Number 23 Year 2006 Regarding Population Administration.